CLINICAL CORRELATIONS BETWEEN GASTROESOPHAGEAL REFLUX DISEASE AND CHILDREN'S THROAT AND LARYNX CONDITION - Yu.L. Soldatskiy; I.E. Pogosova; T.G. Zaviktorina; E.K. Onufrieva (Union of pediatricians of Russia, 2009)
In order to study the impact exerted by the gastroesophageal reflux disease (GERB) on the throat and larynx status, the authors examined 39 children (main group), suffering from GERB, and 15 patients (control group), suffering from the chronic gastrointestinal tract pathology, who did not confirm GERB. All the patients underwent a 24'hour рН-monitoring of the esophagus and laryngeal part of the throat and upper airways endoscopy. They discovered that for the children, suffering from the extraesophageal GERB (i.e. regurgitation of the sourreflux substance above the upper esophageal sphincter into the hypopharynx), it is also typical for chronic throat and larynx pathology: the endoscopy identified the accompanied pathology among 80%, chronic pharyngitis among 62,5%, and their combination among 48% of patients. Normalization of an mucous membrane of esophagus is highly likely to correlate (r = 0,54, р<0,01) with the throat and larynx status normalization. Thus, it is very likely that GERB and its extraesophageal variant in particular plays a great role in pathogenesis of the throat and larynx disease development. This circumstance should be consider both in therapy of the patients with GERB and detection of pathologies in the ENT organs.Key words: gastroesophageal reflux, chronic pharyngitis, chronic laryngitis, children.